2021
DOI: 10.15446/agron.colomb.v39n3.91841
|View full text |Cite
|
Sign up to set email alerts
|

Co-inoculation with a product based on native microorganisms improves germination and seedling growth of Phaseolus vulgaris L.

Abstract: Agricultural products based on native microorganisms represent an ecological alternative to traditional chemical fertilizers for enhancing growth and crop yield. This study aimed to evaluate the effect of the product based on native microorganisms IHPLUS® on germination, emergence, and primary leaf formation of Phaseolus vulgaris L. seedlings. The treatments consisted of a control (immersion in distilled water) and nine treatments that were the combination of IHPLUS® at three concentrations and three immersion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…(2018) reportaron que es efectiva la sustitución hasta used in agriculture for their beneficial effect on the growth and productivity of several plant species, such as tobacco (Calero-Hurtado et al, 2019) and beans (Calero-Hurtado et al, 2020). Another study was reported by Díaz-Solares et al (2019) who used IH-Plus® to improve sorghum and reported very encouraging results for this species. Thus, the use of these organic products is important in nutrient management in integrated livestock-agriculture systems, in addition to making a correct use of the utilization of the resources available on the farm and once again demonstrating that diversified and integrated systems place greater emphasis on the optimal use of the available local resources.…”
Section: Resultados Y Discusiónmentioning
confidence: 91%
See 1 more Smart Citation
“…(2018) reportaron que es efectiva la sustitución hasta used in agriculture for their beneficial effect on the growth and productivity of several plant species, such as tobacco (Calero-Hurtado et al, 2019) and beans (Calero-Hurtado et al, 2020). Another study was reported by Díaz-Solares et al (2019) who used IH-Plus® to improve sorghum and reported very encouraging results for this species. Thus, the use of these organic products is important in nutrient management in integrated livestock-agriculture systems, in addition to making a correct use of the utilization of the resources available on the farm and once again demonstrating that diversified and integrated systems place greater emphasis on the optimal use of the available local resources.…”
Section: Resultados Y Discusiónmentioning
confidence: 91%
“…Los mismos se han utilizado en la rama de la agricultura por su efecto benéfico en el crecimiento y la productividad de varias especies de plantas, como el tabaco (Calero-Hurtado et al, 2019) y en frijol (Calero-Hurtado et al, 2022). Otro estudio fue el reportado por Díaz-Solares et al (2019), quienes emplearon el IH-Plus® para to animal grazing. However, from the first year on, production began to be obtained from several crops that were planted in this area for self-consumption.…”
Section: Resultados Y Discusiónunclassified